SAT0243 Endothelial dysfunction reflected by high S-ICAM-1 and VWF levels accelerates coronary atherosclerosis in systemic lupus erythematosus patients. (23rd January 2014) - Plazak, W.; Gryga, K.; Olszowska, M.; Mazurek, A.; Konieczynska, M.; Sznajd, J.; Milewski, M.; Musial, J.; Podolec, P.
Abstract : Background: Conventional risk factors of coronary artery disease fail to explain accelerated atherosclerosis in systemic lupus erythematosus (SLE) patients. Clinical and experimental studies shows that soluble intercellular adhesion molecule 1 (sICAM-1) and von Willebrand factor (vWF) levels reflect endothelial damage or dysfunction. Objectives: This study was conducted to determine the possible influence of endothelial pathology assessed by sICAM-1 and vWF levels on coronary artery calcifications in SLE patients. Methods: In 60 SLE patients in stable clinical conditions, without a prior history of coronary artery disease, MultiDetector Computed Tomography (MDCT)-based coronary calcium scoring was performed. Laboratory evaluation included serum concentrations of sICAM-1, vWF, C-reactive protein (CRP) and antinuclear antibodies (ANA) titers. Results: MDCT revealed coronary calcifications in 15 (25%) patients. Calcium scores ranged from 0.3 to 843.2 (median 31, 7). No association was found between these scores and conventional coronary artery disease risk factors (obesity, hypertension, tobacco use, hyperlipidaemia, diabetes) nor CRP levels. On the contrary, as compared to patients with calcium score =0, in those with coronary calcifications higher concentrations of sICAM-1 (382.2±328.2 vs. 267.1±62.7, p=0.01), vWF (188.5±87.6 vs. 149.2±52.2, p=0.025) and higher ANA titers (8320±4521 vs. 4668±2717, p=0.03) were found. Conclusions: Conventional risk factors of coronary artery disease as well as markers of an ongoing inflammation do not show significant association with coronary artery calcifications in SLE patients. Calcified atherosclerotic plaques were observed mainly in patients with elevated levels of sICAM-1, vWF or high ANA titers. The sICAM-1 and vWF levels may serve as a possible risk marker of coronary calcifications and may have a prognostic importance. Disclosure of Interest: None Declared